EUROPEAN INTEGRATION AND THE REFORM OF THE UKRAINIAN EDUCATIONAL SECTOR - Ihor Hasiuk; Iryna Darmanska; Lyudmila Mashkina; Olena Pehota; Maryna Savchenko (Public Policy and Administration, 2022)
In this paper, trends in the development of Ukraine’s education sector in the context of the country’s European integration are revealed. This is accomplished through research into the dynamics of changes in the basic indicators of the development level of the sector in the 1990–2019 period on the basis of state statistical reporting. The purpose of this article is to establish the dynamics and directions of changes in the main indicators of pre-school, general secondary, vocational, and higher education. Further, this article seeks to provide an objective and sound assessment of the public authorities regarding the implementation of the state policy of reforming the Ukrainian education sector in accordance with the European integration concept.